Structure and mask design for 3D RESURF Schottky diode (Thai) - Chantngarm, Peerasak (Asia-Pacific Journal of Science and Technology, 2017)
This paper presents a 3D RESURF Schottky diode structure which is known to have a higher breakdown voltage than that of the conventional 2D RESURF structure. This has been done by adding an alternative pattern of the n-drift Schottky diode and the p-drift Schottky diode in the horizontal direction. In addition, a process simulation has been done, and the masks have been designed for the fabrication of real devices in the future. The simulation results suggest the optimized fabrication process conditions in order to obtain the appropriate dopant distribution required for the realization of the RESURF structure. A process simulation has also been done for a p+ /n+ alternative pattern which is the important part of 3D RESURF structures. Several new ideas, such as using a racetrack structure to facilitate the smooth alternative pattern of the n-drift and p-drift Schottky diodes, have been introduced in the mask design. The goal of the mask design is to further increase the breakdown voltage of this 3D RESURF Schottky diode structure.